Adhesions of pacing catheter to tricuspid valve: adhesive endocarditis - Friedberg, H. David (1969)
A case is reported in which the presence of endocardial pacemaker catheter electrodes provoked an unusual reaction—an adhesive endocarditis. Two pacemaker catheters were in the right ventricle during the last nine months of life. The normal reaction to these foreign bodies of fibrin deposition and endothelialization was intensified so that the first catheter could not be removed after 17 days. Because one catheter was introduced from the left side of the neck, it lay in a commissure of the tricuspid valve to which it was firmly adherent. This constitutes a potential hazard if the removal of the catheter is forcibly attempted, although it does not interfere with the function of the tricuspid valve. Despite this, thrombosis was absent and generally is not a problem with modern materials.